Taxation and the American Revolution - John Passant (Australasian Accounting, Business and Finance Journal, 2017)
This article looks at the interrelationship between revolution and tax in the context of the American Revolution. It examines the role of ordinary people in demanding, among other things, as part of wider demands for democracy and equality, no taxation without representation. The article aims to reintroduce the neglected notions of class and class struggle into current discussions and debates about tax and history, putting the people back into academic narratives about the history of taxation and to their place as political actors on history’s stage.
Keywords: Tax; History; USA; American Revolution; Marx; No taxation without representation